Governance: an ‘empty signifier’ or a scientific research programme? with the introduction of Bob Jessop - Offe, Claus (Journal of Public Governance, 2013)
The introduction presents critical insights on the structure and semantics of the concept of governance. The main approaches to understand the concept of governance, in the debate on the modern state and the market, have been examined. Furthermore, the reasons why at present the concept of governance is so popular all over the world, have been explained. The final part of the paper offers some critical observations on the important limitations in the use of the concept of governance both in theory and practice.